(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Survey and determine the sensitivity and specificity of the rapid shallow breathing index in predicting weaning from the ventilator at the Internal Medicine Intensive Care Department, National Children’s Hospital in 2022-2023. Subjects and methods: Retrospective and prospective descriptive study on 106 patients from 30 days to 15 years old, prescribed invasive mechanical ventilation via endotracheal tube for ≥ 24 hours, meeting the criteria to conduct the experiment, natural breathing method. Analyze data using SPSS 20 software. Results: The majority of subjects participating in the study were successfully weaned from mechanical ventilation (92.5%), in which the rate of successful weaning from mechanical ventilation was lower in men (91.9%) than in women (93.7%). After 30 minutes of performing the spontaneous breathing test, the average RSBI_30 value of the failed ventilator weaning group (6.97 ± 0.72 breathing rate/ml/kg/min) was higher than the successful weaning group work (6.08 ± 1.26 breaths/ml/kg/min) with p = 0.01. Besides, rapid shallow breathing index after 30 minutes of spontaneous breathing trial (RSBI_30) predicts successful weaning from mechanical ventilation with an area under the ROC curve of 0.84; 95% confidence interval is 0.69-0.98; sensitivity 86.7%; specificity 62.5%. Conclusion: It is necessary to combine shallow tachypnea index with other indexes in deciding to wean off the ventilator for pediatric patients treated at the intensive care unit. Do not use it alone to evaluate the prognosis of success when weaning off the ventilator, but need to combine other factors.